Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Perilaku Siswa - Sari, Putri Maharani Anom; Mugiyono, Mugiyono (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This study aims to explore the significant impact of Islamic education learning on student behavior. The methodology employed in this study is a quantitative approach through sample selection. Sample selection among students was conducted using purposive sampling methods. The findings of this study indicate that there is a moderate impact of Islamic education learning on student behavior, with an analyzed influence level of 0.593 or 59.34%. In conducting the analysis, the product moment correlation technique was applied. From the Product Moment